Role of Bacterioferritin & Ferritin in M. tuberculosis Pathogenesis and Drug Resistance: A Future Perspective by Interactomic Approach - Sharma, Divakar; Bisht, Deepa (Frontiers in Cellular and Infection Microbiology, 2017)
Tuberculosis is caused by Mycobacterium tuberculosis, one of the most successful and deadliest human pathogen. Aminoglycosides resistance leads to emergence of extremely drug resistant strains of M.tuberculosis. Iron is crucial for the biological functions of the cells. Iron assimilation, storage and their utilization is not only involved in pathogenesis but also in emergence of drug resistance strains. We previously reported that iron storing proteins (bacterioferritin and ferritin) were found to be overexpressed in aminoglycosides resistant isolates. In this study we performed the STRING analysis of bacterioferritin & ferritin proteins and predicted their interactive partners {ferrochelatase (hemH), Rv1877 (hypothetical protein/probable conserved integral membrane protein), uroporphyrinogen decarboxylase (hemE) trigger factor (tig), transcriptional regulatory protein (MT3948), hypothetical protein (MT1928), glnA3 (glutamine synthetase), molecular chaperone GroEL (groEL1 & hsp65) and hypothetical protein (MT3947)}. We suggested that interactive partners of bacterioferritin and ferritin are directly or indirectly involved in M.tuberculosis growth, homeostasis, iron assimilation, virulence, resistance and stresses.